Aspek ekonomi usaha budidaya rumput laut eucheuma cotonii di Desa Liya Togo Kecamatan Wangi-wangi Selatan Kabupaten Wakatobi - Oliviati, Wa Ode; La Ola, La Onu; Piliana, Wa Ode (Jurnal Sosial Ekonomi Perikanan, 2022)
The purpose of this research is to assess the amount of cost and revenue and to assess the profit of the fishermen's business every time of production. This research was conducted from October to November 2019 in Liya Togo Village, South Wangi-Wangi District, Wakatobi Regency. The method in this study uses a quantitative method by calculating using the formula TC = TVC + TVC and calculating the profit of seaweed farming fishermen using the formula (π) = TR-TC. The data analysis used in this study is the R / C ratio and profit analysis. The results of this study indicate an average (TC) of Rp. 4,814,457. The average income (TR) of Rp. 6,048,000. And the average profit (π) is Rp. 1,233,543. The results of this study show that the seaweed cultivation business is feasible to be developed from a financial aspect.